Human Capital Spillovers and the External Returns to Education - Pedro Portugal; Hugo Reis; Paulo Guimar\~aes; Ana Rute Cardoso (Institute of Labor Economics (IZA), 2025)
We employ a regression model with spillover effects to show that the impact of peer quality on wages is quite large. We estimate that a 10 percent increase in peer quality implies a 2.1 percent increase in an individual's wage. In addition, we estimate the external returns to education using a novel identification strategy, which is strictly based on the peer effect channel, netting out the role of homophily and labor market sorting. We show that a one-year increase in the co-workers' education leads to a 0.58 percent increase in wages. We also show that both effects fade smoothly over time.
Keywords: J31; J24; I26; 330; wage distribution; human capital spillovers; external returns to education; peer effects; linked employer-employee data; high-dimensional fixed effects; workplace; job and occupation